The Implementation of Environment-Based Learning in Developing Children's Naturalistic Intelligence at Islamic Kindergarten Bakti 54 Pulau Mainan - Sugiyanti, Sri; Isnaini, Isnaini; Andre, Lesis; Mirdad , Jamal (The Future of Education Journal, 2025)
This research is motivated by the importance of developing naturalistic intelligence in early childhood, particularly in terms of sensitivity to the surrounding natural environment and the ability to identify local flora and fauna. The objectives of this study are:(1) To examine the implementation of environment-based learning in developing children's naturalistic intelligence, (2) To assess the condition of naturalistic intelligence among children at TK Islam Bakti 54 Pulau Mainan, (3) To determine whether environment-based learning can enhance the naturalistic intelligence of children at TK Islam Bakti 54 Pulau Mainan.This study employs a qualitative approach with a descriptive method. The respondents consist of 12 group B students, 2 kindergarten teachers, and several parents, conducted during March–April 2025. Data collection techniques this was carried out through observation, interviews, and documentation. The data was analyzed through the following steps:data reduction, data presentation, and conclusion drawing. The validity of the data on the implementation of environment-based learning to develop naturalistic intelligence is ensured through data triangulation.The research results show that the implementation of environment-based learning has effectively developed the naturalistic intelligence of children at TK Islam Bakti 54 Pulau Mainan. Environment-based learning activities proved to be highly effective in fostering the development of children’s naturalistic intelligence. The children showed great enthusiasm in participating in activities such as observing plants, caring for animals, and exploring the school’s surrounding environment. Based on observations and documentation, the findings revealed that 11 children demonstrated improvement in their ability to recognize and classify living organisms, as well as increased awareness and care for the environment. Assessments of the children’s naturalistic intelligence showed improved scores, with many falling into the very well developed (BSB) category. Additionally, 9 children displayed participation and interest in environmental care activities, falling under the developing as expected (BSH) category. Therefore, the implementation of environment-based learning can effectively develop the naturalistic intelligence of early childhood learners. This study concludes that environment-based learning contributes positively to the development of naturalistic intelligence in children at TK Islam Bakti 54 Pulau Mainan.